[A look at prospective presidentiables ; Back to the fold ; Sampaguita [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1990)
A look at the survey frontrunners for the presidency of the Philippines in 1992. Salonga, Ramos, Santiago, Pimentel and Estrada tell us where they stand. Muslim rebel returness in Mindanao lay down their arms and try out a new life with the help of government programs. Rock star Sampaguita shows us what makes her different.
A look at prospective presidentiables (18 min.) -- Back to the fold (13 min.) -- Sampaguita (11 min.)
Keywords: Sampaguita (Singer); Presidential candidacy; Muslims -- Social conditions. -- Philippines; Politicians -- Philippines